The case of the perilous palace - Stratford, Jordan (Stratford, Jordan. Wollstonecraft Detective Agency, 2018)
Ada's grandmother has shut down the Wollstonecraft Detective Agency until a request from princess Alexandrina Victoria, the future Queen, places them on the trail of her missing sketchbook, in which she records her private thoughts.